Principal Candidates' Reflective Learning During a Full-Time Internship. (June 2023) - Drake, Timothy A.; Ivey, Laura; Seaton, Lacey
In this case study, we explore how principal candidates made sense of their internship by analyzing their weekly reflections during a school year. We found that candidates' views of leadership developed from viewing leadership solely through the lens of making decisions and providing direction, to recognizing that much of the work of a school leader came from building relationships and delegating leadership responsibilities. Candidates' experiences managing student discipline, conducting classroom walkthroughs and teacher evaluations, and leading professional development and professional learning communities (PLCs) were especially developmental. We conclude with implications for preservice training programs and future research.